A vampire and a damsel in distress - Michele Tager; Lauren Nell (Communicare)
The film Twilight produced by Wyck Godfrey, Mark Morgan and Greg Mooradian and directed by Catherine Hardwicke, enjoyed global box office success, and proved particularly popular with female filmgoers. Despite the commercial success of the film, it was derided specifically by feminist critics for its portrayal of women and heterosexual relationships. Within the context of postfeminist views of gender roles, this article explores how selected female South African viewers’ between the ages of 18 and 45 living in Johannesburg perceived the romance between Edward and Bella in the film Twilight (2008). Participants were divided into age-determined focus groups and each participant completed a questionnaire containing a list of questions around the genre of the film, their feelings about individual characters and their reasons for watching the film. Interview data in the form of quotes from individual participants has been included in the article.